Pengaruh profitabilitas dan ukuran perusahaan terhadap kebijakan deviden pada Perusahaan Manufaktur di BEI (2007-2012) - Fitri Yani; Errin Yani Wijaya; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine the influence of company size and profitability on dividend policy and to determine the factors that most strongly influence the dividend policy on manufacturing companies.The population in this study is a manufacturing company that is listed on the indonesia stock exchange in 2007-2012, while the sample in this study only uses 30 manufacturing companies.Data analysis tool used multiple linear regression and hypothesis testing perfomed by t test, F test and derterminasi coeffisecient (R2). Based on the result of the study it was concluded that the profitability and firm size has a significant influence on the partial and simultaneous dividend policy on manufacturing companies. Profitability and size of the company dividend policy has a strong positive relationship that can be seen from the value of the correlation coefficient. Profitability and firm size has major contribution to the company’s dividend policy on manufacturing.Keywords: Dividend policy, profitability, size of company